Penerapan Metode Word and Phrase Level of Training Pada Kasus Dislogia dengan Kondisi Disabilitas Intelektual: Studi Kasus Tunggal - Yulidar Rusdi Rasyid; Shendy Octriviani; Kaisa Azzahra (22020) (Politeknik Arutala Johana Hendarto [d.h. Akademi Terapi Wicara], 2024)
Intellectual developmental delays, previously known as mental retardation, are brain development conditions that affect an individual's ability to think, learn, and function independently. The ability of a dyslogia child with mental retardation, currently known as intellectual disability, to name the word level of nouns can improve expressive language skills, and which are part of verbal communication.